Note—A Note on Modeling the Relationship of Diminishing Returns to Media Overlap for the Media Planning Problem - Lodish, Leonard M. (Management Science, 1975)
A recent article in Management Science by Zufryden [Zufryden, F. S. 1973. Media scheduling: A stochastic dynamic model approach. Management Sci. 19 (12, August) 1395–1406.] describes a media selection and scheduling model which neglects to consider diminishing returns to repeated exposures at the individual level. This note illustrates the problem by example and cautions potential users to inaccuracies that would occur if the model were to be used in practice.